PERSEPSI SISWA KELAS IX TERHADAP EFEKTIVITAS PEMANFAATAN METODE TAHFIDZ DALAM MEMBENTUK AKHLAK MULIA DI SMP ISLAM TAHFIDZ QUR’AN KOTA BIMA - Desi Ariati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study investigates how ninth-grade students at the Islamic Junior High School Tahfidz Qur'an in Kota Bima view the tahfidz method as a means to cultivate noble character. Using a qualitative phenomenological design, data were collected through semi-structured interviews, participant observation, and document review, with purposively selected informants. The results reveal three main dimensions of perception: (1) students view the tahfidz approach as an instrument of spiritual discipline that fosters patience, steadfastness, and intrinsic religious motivation; (2) regular Qur'an memorization practice produces observable changes in daily moral behavior such as more sincere prayers and greater sensitivity to the needs of others; and (3) supportive conditions including a supportive Islamic boarding school environment, teacher guidance, and active parental involvement significantly enhance the program's impact. These findings suggest that, when combined with systematic evaluation and strong collaboration among all stakeholders, the tahfidz method serves as an effective framework for character development at the junior high school level. This study expands the literature on Islamic moral education and provides actionable recommendations for Islamic institutions aiming to optimize similar programs.